A case report of ovarian granulosa cell tumor in patient with polycystic ovarian syndrome. Issue 50 (17th December 2021) - Kim, Yun S.; Lee, Ji H.
Abstract: Rationale: Granulosa cell tumors (GCTs) account for less than 2% of all ovarian malignancies and are the second most common ovarian sex cord stromal tumors after fibroma/thecomas. GCTs occur most frequently in postmenopausal women with a peak age of 50 to 55, are usually diagnosed in their early stages, and have a good prognosis. GCTs usually present with features of hyperestrogenism, with an average size is 10 to 15 cm. Patient concerns: A 31-year-old nulligravida diagnosed with polycystic ovarian syndrome (PCOS) 10 years prior, had a 20-mm mass in her right ovary found on ultrasonography 2 years ago. She had been taking dienogest 2 mg for 2 years for a misdiagnosed endometrioma, but over a 2-year course, the mass increased to 50 mm. Diagnoses: An ultrasound scan revealed a 47 × 37-mm round solid mass in the right ovary with a spongiform appearance and little vascularity. The pathologic findings showed an adult-type granulosa cell tumor with necrosis and hemorrhage. The tissue stained positive for inhibin-α, Wilms' tumor-1, CD56, and negative for cytokeratin 7. Interventions: We finally performed right salpingo-oophorectomy, endometrial biopsy, peritoneal biopsy, and partial omentectomy. The pathological findings were adult-type granulosa cell tumor. The International Federation of Gynecology and Obstetrics staging was IA. The patient did not require additional treatment. Outcomes: Surprisingly, her normal menstruation returned 2 weeks after the operation, and she had a normal pregnancy and parturition. The patient had been followed-up regularly for 3 years following the surgery. The patient has not experienced any complications and has remained disease-free. Lessons: GCTs should be considered in the differential diagnosis if a female patient with PCOS and amenorrhea shows a unilateral small solid mass. They are extremely rare malignant ovarian tumors that must be differentiated from other benign ovarian tumors, especially endometriomas and dermoid cysts. It was difficult for us to suspect a granulosa cell tumor because the patient already had PCOS symptoms such as mild hirsutism and amenorrhea. This case highlights the importance of physicians being aware of and suspicious for GCTs in similar cases, along with knowing their characteristics in considering possible differential diagnoses.